Enhanced thermal stability of dielectric and energy storage properties in 0.4BCZT-0.6BTSn lead-free ceramics elaborated by sol-gel method. (June 2023) - Khardazi, S.; Zaitouni, H.; Neqali, A.; Lyubchyk, S.; Mezzane, D.; Amjoud, M.; Choukri, E.; Lyubchyk, S.; Kutnjak, Z.
Abstract: Polycrystalline lead-free Ba0.85 Ca0.15 Zr0.10 Ti0.90 O3 (BCZT), BaTi0.89 Sn0.11 O3 (BTSn) and 0.4Ba0.85 Ca0.15 Zr0.10 Ti0.90 O3 –0.6BaTi0.89 Sn0.11 O3 (0.4BCZT–0.6BTSn) ferroelectric ceramics were prepared via sol-gel process and their structural, dielectric and energy storage properties were studied. Pure perovskite structure was confirmed by X-ray diffraction analysis. The evolution of energy storage performances with temperature was studied. A Significant recoverable energy-storage density of 137.86 mJ/cm 3 and high energy-storage efficiency of 86.19% under a moderate electric field of 30 kV/cm were achieved in the composite 0.4BCZT–0.6BTSn ceramic at 353 K. Moreover, excellent temperature stability (70–130 °C) of the energy storage efficiency (less than 3%) was achieved. Highlights: Rietveld refinement results of the 0.4BCZT–0.6BTSn sample indicate the coexistence of the rhombohedral and orthorhombic phases at room temperature. Improved recoverable energy density and energy storage efficiency of 137.86 mJ/cm 3 and 86.19%, respectively under 30 kV/cm were found in the designed 0.4BCZT–0.6BTSn ceramic. 0.4BCZT–0.6BTSn ceramic presents excellent thermal stability of the energy storage efficiency (less than 3%) in the temperature range (70–130 °C). Combining various phases is a promising strategy to enhance energy storage capacities.